Learning English Through Islamic Historical Content - Kuzairi (Adabuna : Jurnal Pemikiran dan Pendidikan, 2022)
This study aims to describe the implementation of Content-based Instruction (CBI) for learning English. it was applied to facilitate students in learning English by providing them as much as language exposure on the content of a subject related to their major in Islamic education. The content deals with an Islamic history on the Hijrah of the Prophet Muhammad (pbuh). The activities were carried out in 3 major stages. The earlier activities were the vocabulary building and grammatical focus on the use of simple past tense. The second section was learning receptive and productive English skill activities covered reading comprehension, practices on speed reading and reading aloud as well as writing summary. At last, this instruction also revealed and discussed the moral values found in the passage about the Hijrah of the Prophet Muhammad (pbuh).